Impact of metals on corrosive behavior of biodiesel-diesel- ethanol(BDE) alternative fuel - Thangavelu, S.K.; Abu Saleh, Ahmed; Farid Nasir, Ani (Elsevier Ltd., 2016)
Corrosive behavior of biodieseledieseleethanol (BDE) fuel blends upon exposure to metals, namely, mild steel, copper and aluminum was studied by static immersion at room temperature and 60 C. The change of fuel properties, i.e., total acid number, density, viscosity, calorific value, flash point, and color changes were investigated. Moreover, fuel compositional changes, such as water content, oxidation product level, and metal elements in the fuel blends were examined. Finally, the effect of fuel blends on corrosion rate (CR), morphology of corrosion products, and chemical structure of metals were studied. Results revealed that the CR of metals in BDE fuels is in the order: aluminum < mild steel < copper at both temperature conditions. The degradation of fuel properties and corrosion rate of metals in BDE fuel blends are lower than neat biodiesel (B100), whereas higher than petroediesel (B0). Corrosiveness of B20D75E5 is lower than B20D70E10 upon exposure to metals.